A framework for organizational architecture - Javier Efrain Gonzáles Alarcon (2013)
This thesis aims to propose a framework that helps to conceive an organization. A framework is a collection of items put together for the same purpose and organizations are social units deliberately constructed and reconstructed to seek specific goals. There are systematic approaches that address product systems conception but not organization systems conceptions. Existing organization conception approaches either emphasizes too much the strategic aspect or emphasizes too much the process aspects. However, very few take into consideration in a systematic way informational and resources aspects. This thesis considers the organization in the physical world as composed by an integrated set of resources. The framework proposed has three dimensions: the analysis dimension that covers strategic, process, informational and structural analysis of the organization; the integration dimension that integrates the physical, financial, intangible and human resources; the abstraction dimension that recognizes the various hierarchical layers in the organization. The framework was applied to model a real organization by the use of a detailed step by step method adherent to the framework. Conclusions are that the model framework covered all necessary aspects to model an organization.